PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT DENPASAR SELATAN - I Ketut Dandi Payana; Pande Ketut Ribek; Tiksnayana Vipraprastha (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Work motivation an encouragement or process that is carried out to move someone so that their behavior can be directed at real efforts so that goals can be achieved, to produce good and quality performance. Human resources are needed who have work motivation, work discipline, and a supportive work environment. This research aims to determine the effect of work motivation, work discipline and work environment on employee performance in the South Denpasar District Office The population used in this study were employees in the South Denpasar District Office. The sample payment method used is a saturated sample with a total of 41 respondents. Data collection techniques using observation, interviews and questionnaires. The data analysis technique used in this research is multiple linear regression analysis technique. This study also carried out descriptive statistical analysis and classical assumption tests which included normality, multicollinearity, and heteroscedasticity assumption tests and used hypothesis testing including the F test, coefficient of determination test and t test. The results showed that the variable work motivation has a positive and significant effect on employee performance variables work discipline has a positive and significant effect on employee performance variables the work environment has a positive and significant effect on employee performance variables